0106 Alternative Technologies In Simulation. (1st November 2014) - Gay, Christopher; Riby, Stuart; Graby, Matthew; Purva, Makani
Abstract : Background: Whilst simulation technology can be very much 'off the shelf', there are many possibilities to integrate non-standard technologies into simulation training, often at little cost and with great benefit to the effectiveness of training. At HILS we are lucky enough to have access to alternative technologies. Innovations and outcomes: The following alternative technologies have been used to enhance simulation: Go pro camera – usually used in extreme sports, we have used it to get unique perspectives on simulation – this has provided a lot of footage to be used in training videos where a standard video camera would not have been able to fit Bluetooth audio- cheap Bluetooth wireless audio enables environmental sounds such as ambulances or patients talking to be played from a mobile phone or tablet to increase fidelity in simulations Google Hangouts- Google's free web conferencing software enables us to host geographically unlimited but feature-full simulation debriefing sessions Blackout function – the existing surgeons panel in simulated theatre was reprogrammed to switch all the lights off at once, emulating blackout scenarios. Combined with infra-red cameras the resulting session can be still seen. Take-home messages: Using trial and error, some new technologies can be integrated into simulation with great effect Often for little cost a big impact can be realised Augmenting simulation with other technologies helps us learn that the limits of individual pieces of equipment can be worked around Reference: Dr Makani Purva – HILS